Farmers' Behavior in the Application of Coffee Harvest and Post-Harvest Techniques According to Good Manufacturing Practice Quality Standards - Abdullah Al Azis; Dadan Dwi Pratama; Reza Zaini Fadhilah; Dwi Purnomo; Dodi Budirokhman (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Good manufacturing practice is a guideline for producing safe and quality food products. GMP is carried out from the plantation, starting from harvest and post-harvest techniques. Harvest and post-harvest handling is influenced by the farmer's behavior in carrying out his business. This research aims to determine the behavior of farmers in Cilimus District in implementing coffee harvesting and post-pane techniques in accordance with GMP standards. The research was conducted in Cilimus District, Kuningan Regency with the consideration that this area has superior coffee production. The research is planned to be carried out in January 2024. The research design used is descriptive quantitative with survey research techniques. The sample size in this study was 65 respondents. The data analysis technique was carried out descriptively with a Likert score weighting of 1-5. The research results show that farmer behavior in harvesting techniques consists of knowledge with a percentage of 56.31%, attitude with a percentage of 52.00% and farmer skills with a percentage of 49.78%. Each aspect indicates quite good condition. Farmers' behavior in post-harvest handling consists of knowledge of 64.09% in the good category, but attitude of 55.87% and skills of 50.86% in the quite good category